FAKTOR-FAKTOR YANG MEMPENGARUHI STRUKTUR MODAL (Studi pada Perusahaan Manufaktur yang Terdaftar di BEI Periode 2014-2016) - Hesti Irwandani, 14.05.52.0199; Poerwati, Tjahjaning. (Students' Journal of Accounting and Banking, 2018)
This study examines the effect of non debt tax shield, liquidity, profitability, asset growth, firm size and institutional ownership on capital structure. The purpose of this study is to determine the factors that influence the capital structure of manufacturing companies listed on the Indonesia Stock Exchange. The research sample used in this study was purposive sampling and obtained data as many as 62 companies. Data analysis techniques using multiple linear regression. The results of the study show that the variables of non debt tax shield and institutional ownership have a positive and not significant effect on the capital structure. Liquidity and profitability have a significant negative effect on the capital structure. While the growth of assets and company size has a significant negative effect on the capital structure Keywords: Non Debt Tax Shield, Liquidity, Profitability, Growth of Assets, Company Size and Institutional Ownership